2013
DOI: 10.2528/pier12082305
|View full text |Cite
|
Sign up to set email alerts
|

Sparse Array Microwave 3-D Imaging: Compressed Sensing Recovery and Experimental Study

Abstract: Abstract-Microwave array 3-D imaging is an emerging technique capable of producing a 3-D map of scattered electric fields. Its all-weather and large scene imaging features make it an attractive powerful tool for target detection and feature extraction. Typically, a microwave array 3-D imaging system based on the classical sampling theory requires a large dense 2-D antenna array, which may suffer from a very high cost. To reduce the number of the antenna array elements, this paper surveys the use of compressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…CS has also been successfully deployed in track-beforedetect radar systems, which reconstruct the whole radar scene from sparse measurements [12]. Also using CS, low-cost high-quality sparse array 3-D microwave imaging have recently been shown to be feasible [13].…”
Section: Introductionmentioning
confidence: 99%
“…CS has also been successfully deployed in track-beforedetect radar systems, which reconstruct the whole radar scene from sparse measurements [12]. Also using CS, low-cost high-quality sparse array 3-D microwave imaging have recently been shown to be feasible [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, considering that the 2-D/3-D radar imaging techniques have been used more and more [16,17], the imaging based RCS measurement results are more practical and useful than the electromagnetic computing results.…”
Section: Complicated Flight Modementioning
confidence: 99%
“…A great deal of compressed sensing based methods have been applied to radar systems [8][9][10][11][12][13][14][15][16][17][18], which recover the target scene from fewer measurements than traditional methods. In [8], it is demonstrated that the compressed sensing can eliminate the need for matched filter at the receiver and has the potential to reduce the required sampling rate.…”
Section: Introductionmentioning
confidence: 99%
“…[10] focuses on monostatic chaotic multiple-input-multiple-output (MIMO) radar systems and analyze theoretically and numerically the performance of sparsity-exploiting algorithms for the parameter estimation of targets at Low-SNR. In the context of synthetic aperture radar (SAR), [11][12][13][14][15][16] present compressed sensing based data acquisition and imaging algorithms. An additional sensing matrix H is introduced in [17,18], which compress the received signal further by making nonadaptive, linear projections of the direct data sampled at the Nyquist frequency.…”
Section: Introductionmentioning
confidence: 99%